Faktor Internal Perusahaan yang Berpengaruh Terhadap Kepuasan Pelanggan pada Perusahaan Bahan Kimia di Kota Malang - Rugeri Fadhli Halim (Jurnal VOK@SINDO, 2018)
This study aims to analyze some of the company's internal factors which include corporate marketing strategy and technology used to provide service quality at a chemical distribution company in Malang. The method used in this research is quantitative method by doing explanatory research. The population covers the consumers who have already made a transaction at the company that become the object of research. The sample used is the representativeness sample involving 100 respondents. The results show that company's internal factors significantly influence the quality of the service. Morever, technology also affects the accuracy of providing information for consumers in order to improve the quality of the service.